The chromatin reader protein ING5 is required for normal hematopoietic cell numbers in the fetal liver - Mah, Sophia Y.Y.; Vanyai, Hannah K.; Yang, Yuqing; Voss, Anne K.; Thomas, Tim (Frontiers in Immunology, 2023)
ING5 is a component of KAT6A and KAT7 histone lysine acetylation protein complexes. ING5 contains a PHD domain that binds to histone H3 lysine 4 when it is trimethylated, and so functions as a ‘reader’ and adaptor protein. KAT6A and KAT7 function are critical for normal hematopoiesis. To examine the function of ING5 in hematopoiesis, we generated a null allele of Ing5. Mice lacking ING5 during development had decreased foetal liver cellularity, decreased numbers of hematopoietic stem cells and perturbed erythropoiesis compared to wild-type control mice. Ing5–/– pups had hypoplastic spleens. Competitive transplantation experiments using foetal liver hematopoietic cells showed that there was no defect in long-term repopulating capacity of stem cells lacking ING5, suggesting that the defects during the foetal stage were not cell intrinsic. Together, these results suggest that ING5 function is dispensable for normal hematopoiesis but may be required for timely foetal hematopoiesis in a cell-extrinsic manner.